IDENTIFIKASI BURNOUT SYNDROME PERAWAT DI LINGKUNGAN ALIANSI RS ISLAM JAKARTA - Dewi; Kamil, Abdu Rahim; Lianda, Inge Cahaya; Silaban, Nataria Yanti; Wulansari, Novia (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Nursing is a demanding and stressful profession that can lead to burnout, which has a negative impact on the well-being of nurses and the quality of patient care. Jakarta Islamic Hospital is known as a hospital with a high patient burden, which can lead to the prevalence of burnout among nurses. This study aims to identify the prevalence of burnout syndrome among nurses working in three Islamic Hospitals in Jakarta. The study is a cross-sectional study using the Maslach Burnout Inventory to measure three dimensions of burnout: emotional exhaustion, depersonalization, and personal accomplishment. This study involved 222 nurses from the Aliansi Hospital of Jakarta Islamic Hospital. Data was taken from January to February 2023. The results in this study showed that the average score for emotional exhaustion was 13.55, depersonalization was 8.46, and personal achievement was 33.40. These findings indicate that nurses at the Jakarta Islamic Hospital experience high levels of burnout, especially emotional exhaustion and depersonalization. This study highlights the need for hospital management to implement interventions to prevent and manage burnout among nurses, which can lead to improved patient care and a better quality of life for healthcare workers.